How Invasive is the Free Gracilis Muscle Flap? A Prospective Study on Donor Site Morbidity - Wachtel, Nikolaus; Giunta, Riccardo E.; Hirschmann, Maximilian; Hellweg, Marc; Nuernberger, Tim; Moellhoff, Nicholas; Ehrl, Denis (Journal of Reconstructive Microsurgery, 2025)
Free gracilis muscle (GM) flaps represent a reliable workhorse procedure in the field of plastic and trauma surgery. However, only a small number of studies have examined this large group of patients regarding the morbidity of flap harvest. The aim of this prospective study was therefore to objectively investigate the morbidity of free GM flaps.A control group (n = 100) without surgery was recruited to assess interindividual differences in strength and range of motion (ROM) in the hip and knee joint (dominant vs. nondominant side). Additionally, for 50 patients with free GM flap surgery, these parameters were assessed in an identical manner.The control group showed significant interindividual differences in strength for abduction and adduction in the hip joint when comparing the dominant to the nondominant side, but no significant differences in the ROM. GM flap harvest led to no significant differences in maximum force 20.3 (± 13.8) months after surgery in all parameters/movements that were assessed. However, the ROM for abduction in the ipsilateral hip joint was significantly reduced after surgery.The GM flap has a low donor site morbidity and should therefore be considered as a first-line option for microsurgical reconstructive procedures. Moreover, the low morbidity is not affected by preexisting differences in strength when comparing the dominant to the nondominant side.
Keywords: gracilis muscle flap; donor site morbidity; free flap morbidity; strength and ROM after gracilis muscle flap